Theatre efficiency in COVID- 19 pandemic conditions: The collaborative experience of four level 1 major trauma centres in the UK. (2021) - Jeyaseelan, L.; Sedgwick, P.; Daly, I. El-; Tahmassebi, R.; Pearse, M.; Bhattacharya, R.; Trompeter, A. J.; Bates, P.
No abstract available